PENYELESAIAN SENGKETA KONSUMEN MELALUI BADAN PENYELESAIAN SENGKETA KONSUMEN (BPSK) DALAM TRANSAKSI E-COMMERCE: Studi Kasus BPSK DKI Jakarta - Sania Athilla (2022)
The amount of consumer disputes involving e-commerce transactions demonstrate the relevance of consumer protection in this area. This tendency causes a power imbalance between business actors and customers. The fact that customers are frequently at a lower level than business actors. These attempts to safeguard consumers can be passed in. There are two options: going to court or going out of court. The goal of this paper is to learn about the Settlement Agency Consumer Disputes BPSK efforts to resolve consumer disputes in e-commerce transactions and to learn about consumer protection against e-commerce transaction disputes at DKI BPSK Jakarta. The research method used in this paper is the normative juridical method, which uses a legislative approach and a case approach to collect data using procedures such as literature review, observation, and interviews, which are then analyzed descriptively and qualitatively. The findings of this study suggest that BPSK can be used in conjunction with conciliation, mediation, and arbitration attempts to resolve consumer conflicts involving e-commerce. Consumer protection procedures in the scenarios described in BPSK DKI Jakarta No. 036/PNTP/BPSK-DKI/VI/2020 are insufficient since situations like this require not only consumer protection and civil affairs, but also criminal action.